Infection of red foxes with Echinococcus multilocularis in western Switzerland - Brossard, Michel; Andreuttia, C.; Siegenthaler, M. (My University, 2007)
In the Jura mountains, Plateau and Alps of western Switzerland important variations in the prevalence of Echinococcus multilocularis infection in red foxes were observed between geographical areas from 1990 to 1995. The Jura mountains and the Plateau had higher mean prevalence levels than the Alps with 30.6, 32.4 and 18.8%, respectively. The highest rate was recorded in the Plateau in the canton of Fribourg with a prevalence of 52.3%. The prevalence of E. multilocularis infection in foxes in the alpine canton of Valais was the lowest (7.1%). Juvenile foxes were found to be more susceptible to E. multilocularis than adults. Adult foxes were less heavily infected in summer and autumn, while the prevalence in juveniles (less than 1 year old) increased between the spring and winter, when they are more than 6 months old. The retrospective data relate to the beginning of the 1990s, since when a drastic prevalence increase of E. multilocularis infection in foxes has occurred in several regions of Europe. Nevertheless, the study is a major contribution to the epidemiological situation of E. multilocularis in central Europe, in that it contains valuable information on spatial distribution and seasonal differences in different age groups of foxes.